Gorgonias y corales pétreos (Anthozoa: Gorgonacea y Scleractinia) de Cabo Pulmo, México - Reyes Bonilla, Héctor (Universidad de Costa Rica, 1997)
A systematic list of the species of Gorgonacea and Scleractinia reported at Cabo Pulmo reef, Pacific coast of México (23.5° N, 109.5° W), is presented. Data were obtained from literature revisions and field work conducted between 1986 and 1997. A total of ten species of gorgonians and 12 of stony corals are currently known at the site. As richness levels of scJeractinians seem to have changed little in decades, this reef system can be considered one of the most stable of the eastern Pacifico